The Impact of Ethical Norms on Relationship Quality and Commitment in Malaysia’s Legal Service Sector and the Moderating Effect of Ethical Ideologies - Abdullah, Rebecca Lai (2010)
In light of relatively recent high profile cases where the centre of controversy is the ethical standards of professionals (lawyers and accountants), ethical behaviour of professionals have been closely monitored around the world. Lawyers therefore should have an understanding of how ethical behaviour may affect the success or failure of their organisation. This paper provides empirical evidence and argument for lawyers that behaving ethically is a relationship marketing strategy that should be adopted in order to enhance the value of their organisation by increasing the quality of their relationship with customers and obtaining customer commitment. This paper also provides empirical evidence and argument for lawyers that ethical ideologies generally do not moderate the relationship between ethical norms and relationship quality and commitment. For this paper, a questionnaire survey was used to collect data from customers of lawyers to determine their perception of lawyers’ ethical norms, their views on relationship quality and commitment. It also classifies customers according to ethical ideology. Regression analysis was used to test the relationships between ethical norms, relationship quality and commitment as well as to the moderating effect of ethical ideologies on these relationships. The results of this study hold significant implications for existing ethical theories, legal practitioners and policy makers.